Libvdwxc: a library for exchange–correlation functionals in the vdW-DF family. (7th June 2017) - Larsen, Ask Hjorth; Kuisma, Mikael; Löfgren, Joakim; Pouillon, Yann; Erhart, Paul; Hyldgaard, Per
Abstract: We present libvdwxc, a general library for evaluating the energy and potential for the family of vdW-DF exchange–correlation functionals. libvdwxc is written in C and provides an efficient implementation of the vdW-DF method and can be interfaced with various general-purpose DFT codes. Currently, theGpaw and Octopus codes implement interfaces to libvdwxc. The present implementation emphasizes scalability and parallel performance, and thereby enables ab initio calculations of nanometer-scale complexes. The numerical accuracy is benchmarked on the S22 test set whereas parallel performance is benchmarked on ligand-protected gold nanoparticles ( Au 144 ( SC 11 NH 25 ) 60 ) up to 9696 atoms.